Pathophysiological mechanisms of Staphylococcus non-aureus bone and joint infection: interspecies homogeneity and specific behaviour of S. pseudintermedius - Yousef Maali; Yousef Maali; Patrica Martins-Simoes; Patrica Martins-Simoes; Florent Valour; Florent Valour; Daniel Bouvard; Daniel Bouvard; Michele Bes; Marisa Haenni; Tristan Ferry; Tristan Ferry; et al. (Frontiers in Microbiology, 2016)
Implicated in more than 60% of bone and joint infections (BJIs), Staphylococci have a particular tropism for osteoarticular tissue and lead to difficult-to-treat clinical infections. To date, Staphylococcus aureus internalization in non-professional phagocytic cells (NPPCs) is a well-explored virulence mechanism involved in BJI chronicity. Conversely, the pathophysiological pathways associated with Staphylococcus non-aureus (SNA) BJIs have scarcely been studied despite their high prevalence. In this study, fifteen reference strains from 15 different SNA species were compared in terms of (i) adhesion to human fibronectin based on adhesion microplate assays and (ii) internalization ability, intracellular persistence and cytotoxicity based on an in vitro infection model using human osteoblasts. Compared to S. aureus, Staphylococcus pseudintermedius was the only species that significantly adhered to human fibronectin. This species was also associated with high (even superior to S. aureus) internalization ability, intracellular persistence and cytotoxicity. These findings were confirmed using a panel of 17 different S. pseudintermedius isolates. Additionally, S. pseudintermedius internalization by osteoblasts was completely abolished in β1 integrin-deficient murine osteoblasts. These results suggest the involvement of β1 integrin in the invasion process, although this mechanism was previously restricted to S. aureus. In summary, our results suggest that internalization into NPPCs is not a classical pathophysiologic mechanism of SNA BJIs. S. pseudintermedius appears to be an exception, and its ability to invade and subsequently induce cytotoxicity in NPPCs could explain its severe and necrotic forms of infection, notably in dogs, which exhibit a high prevalence of S. pseudintermedius infection.